Prediction and Optimization of Process Parameters on Metal Inert Gas of Dissimilar Aluminium Alloy AA6061-T6 and AA7075-T6 using Response Surface Method Analysis - Nur Fakhriah, Mohd Noordin; M., Ishak; L. H., Shah (Trans Tech Publications, Switzerland, 2016)
The aim of this research is to predict the tensile strength of the dissimilar aluminium joint by optimizing the parameters in metal inert gas (MIG) welding between aluminium alloys AA6061-T6/AA7075-T6. In this study, the box-behnken design technique and mathematical model were developed by Response Surface Methodology (RSM). Statistical tools such as Design of Experiments (DOE), Analysis of Variance (ANOVA), and regression analysis were used to develop the relationships. Dissimilar aluminium of AA6061-T6 and AA7075-T6 were butt-welded by using MIG with the ER5183 filler. The highest ultimate tensile strength (UTS) of the joint obtained was 178.63 MPa